(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2022)
The Big Bang idea is referred in the glorious Quran. As a matter of fact, there is no single integrated model describing the formation of all type of the galaxies. This work proposes a new theory and equations describing the controlling conditions and parameters of stars and galaxies formation. The derived equation called, Sayed`s galaxy formation formula (SGFF), shows that the formation of the major disk (spiral) and elliptical galaxies is correlated to the 2π and 4π geometry of the initial cloud. Sayed`s temperature (Ts) , pressure (Ps) and radius (Rs) are among the effective parameters of galaxies formation. The mass of galaxy (Sayed`s galaxy mass formula- SGME) was also deduced based on acceleration and expansion and given as a new formula. The formulas were validated and verified by check of the units and comparison with the declared values. The minimum mass (0.0774Mʘ) for star formation was calculated and found to be fully matched with the reference range; 0.075 – 0.08 solar mass, for 4π geometry. The gas halo mass of the Milky Way was calculated with 2 % discrepancy. Our previous article; Dark matter-energy to Hydrogen-helium ratio should be considered in galaxy formation mechanism and calculation.